Bacterial meningitis in north India: trends in antimicrobial resistance - Khan, Fatima; Rizvi, Meher; Sultan, Asfia; Shukla, Indu; Malik, Abida (Annals of Pathology and Laboratory Medicine, 2015)
Background: The mortality rate in ABM remains significant and has been reported in the range of 8-40%. It is important to know the regional bacterial etiology in semitropical countries like India along with their sensitivity profile to allow optimum management of such patients. This study was undertaken to evaluate the trends in etiology of bacterial meningitis and the antimicrobial resistance pattern of the pathogens prevalent in North India over a period of 8 years. Material and Methods: The study was performed from June 2001 to June 2009. CSF samples were collected from all patients suspected of meningitis and cultured on chocolate agar, blood agar and MacConkey agar. Antimicrobial susceptibility testing was done using Kirby Bauer disc diffusion method. Detection of MRSA, HLAR, ESBL, AmpC and MBL was also done. Results: 401 samples were positive on culture. S. aureus was the most common pathogen isolated. Among the gram positive cocci as well as the gram negative bacilli a gradual decline in the antimicrobial susceptibility was seen. The aminoglycosides were found to be most effective group of antimicrobial. Towards the end of the study an alarming rise of methicillin resistance in S. aureus to 69.4%, HLAR among the Enterococci to 60% was noticed and among the Enterobacteriaceae ESBL and AmpC production was found to be 16.67% and 42% respectively. Conclusion: The high prevalence of drug resistant pathogens should be dealt with by rational use of antimicrobials. Frequent revision in drug policy may be necessitated for optimum management of patients.